2015
DOI: 10.1371/journal.pone.0118627
|View full text |Cite
|
Sign up to set email alerts
|

Sera from Children with Autism Induce Autistic Features Which Can Be Rescued with a CNTF Small Peptide Mimetic in Rats

Abstract: Autism is a neurodevelopmental disorder characterized clinically by impairments in social interaction and verbal and non-verbal communication skills as well as restricted interests and repetitive behavior. It has been hypothesized that altered brain environment including an imbalance in neurotrophic support during early development contributes to the pathophysiology of autism. Here we report that sera from children with autism which exhibited abnormal levels of various neurotrophic factors induced cell death a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 121 publications
(138 reference statements)
0
13
0
Order By: Relevance
“…Evaluation of neurobehavioral development in rodents represents an essential study paradigm to model neurodevelopmental disorders such as Down syndrome and autism spectrum disorders (ASDs) which are characterized by mental retardation and delays in growth and development787980. In rodents like mice and rats, the early postnatal period is associated with a burst of brain growth, synaptogenesis, myelination, and development of motor and sensory modalities7879.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of neurobehavioral development in rodents represents an essential study paradigm to model neurodevelopmental disorders such as Down syndrome and autism spectrum disorders (ASDs) which are characterized by mental retardation and delays in growth and development787980. In rodents like mice and rats, the early postnatal period is associated with a burst of brain growth, synaptogenesis, myelination, and development of motor and sensory modalities7879.…”
Section: Methodsmentioning
confidence: 99%
“…80. Examination was started on PND1 and was carried out until PND21 (or until the appearance of developmental milestone/neurological reflex) daily between 12:00–15:00 hours in a set up made specifically for the purpose in the Behavior Lab of the Department of Neurochemistry at NYSIBR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a and b), which encodes the cytoskeletal-associated proteins that constitute a link between the membrane and the cytoskeleton involved in the signal transduction pathways. Evidence from functional studies suggest that JAK2 is involved in the JAK-STAT cascade, a process that includes the development, maintenance, and survival of central nervous system glial cells and neurons as well as enhanced brain-derived neurotrophic factor expression (Kaur et al 2005;Kazim et al 2015). Previous studies have demonstrated that JAK-STAT activation signals play a crucial role in ASD immune dysfunction (Ahmad et al 2017), and it was found to participate in the MAPK cascade process (https://www.ncbi.nlm.nih.gov/gene/ 3717) in the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The sera from autistic children also caused significant reductions in the mRNA and protein expression of BDNF in the cerebral cortex of these rats, possibly through increasing oxidative stress by increased amounts of reactive oxygen species and lipid peroxidation present in the sera (Chauhan et al, 2004). Interestingly, a small ciliary neurotrophic factor (CNTF) mimetic, P6, given at the same time as the sera injection, was able to reverse both behavioural and molecular deficits (Kazim et al, 2015). CNTF is thought to assert neuroprotection at least partly via elevating BDNF levels by enhancing its transcription (Bolognin et al, 2012).…”
Section: Autismmentioning
confidence: 99%